〈王鳳儀倫理療病闡析〉一文評析: Review of "On Fengyi Wang’s Ethical Cure" - CAI, Xiangyuan (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. The modern discipline of bioethics is usually understood to represent life and ethics as two intrinsically separate fields. In his article, which clarifies the concept of an ethical cure, Zhang Xianglong takes a novel approach to bioethics, regarding life and ethics as closely intertwined. Zhang’s main aim is to determine whether ethics-based medical treatments are rational and can be scientifically defended. After rejecting the arbitrary claims of scientism, Zhang indicates that the concept of an ethical cure is predicated on an assumption of the unity of heaven and human beings. Although this assumption seems to oppose the traditional Western philosophy of dualism, Zhang argues that the two schemes of thought offer certain common insights into modern life, particularly with reference to pragmatism and phenomenology. DOWNLOAD HISTORY | This article has been downloaded 39 times in Digital Commons before migrating into this platform.